Morinda carnosa (Morindeae-Rubiaceae), a new species from Palawan, Philippines - Venturina, Russell Evan L.; Suarez, Ethan Elijah L.; Alejandro, Grecebio Jonathan D. (Phytotaxa, 2017)
Morinda carnosa, a new species from Mt.Talon, Coron Palawan, Philippines is here described and illustrated. This is a first record of endemic Morinda in the country following the current taxonomic revisions in Morindeae. Morinda carnosa is easily distinguished from other Malesian Morinda by having petals being carnose and thick, corolla lobes not recurved, corolla pubescent with prominent striations on each lobe, calyx puberulent and fruit sparsely scabrid.